Pulse Voltammetry in Physical Electrochemistry and Electroanalysis Theory and Applications - Molina, Ángela; González, Joaquín; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
For the first time, the authors provide a comprehensive and consistent presentation of all techniques available in this field. They rigorously analyze the behavior of different electrochemical single and multipotential step techniques for electrodes of different geometries and sizes under transient and stationary conditions. The effects of these electrode features in studies of various electrochemical systems (solution systems, electroactive monolayers, and liquid-liquid interfaces) are discussed. Explicit analytical expressions for the current-potential responses are given for all available cases. Applications of each technique are outlined for the elucidation of reaction mechanisms. Coverage is comprehensive: normal pulse voltammetry, double differential pulse voltammetry, reverse pulse voltammetry and other triple and multipulse techniques, such as staircase voltammetry, differential staircase voltammetry, differential staircase voltcoulommetry, square wave voltammetry and squarewave voltcoulommetry.
Introduction -- Single Potential Step Voltammetry -- Double and Triple Potential Step Techniques -- Multipotential Step Voltammetry -- Linear and Cyclic Sweep Voltammetry.
Keywords: Electrochemistry; Measurement; Measuring instruments; Analytical chemistry; Electrochemistry; Measurement Science and Instrumentation; Analytical Chemistry